Incorporation of rician noise in the analysis of biexponential transverse relaxation in cartilage using a multiple gradient echo sequence at 3 and 7 tesla. Issue 1 (28th February 2014) - Bouhrara, Mustapha; Reiter, David A.; Celik, Hasan; Bonny, Jean‐Marie; Lukas, Vanessa; Fishbein, Kenneth W.; Spencer, Richard G.
<x xml:space="preserve">Abstract</x> Purpose Previous work has evaluated the quality of different analytic methods for extracting relaxation times from magnitude imaging data exhibiting Rician noise. However, biexponential analysis of relaxation in tissue, including cartilage, and materials is of increasing interest. We, therefore, analyzed biexponential transverse relaxation decay in the presence of Rician noise and assessed the accuracy and precision of several approaches to determining component fractions and apparent transverse relaxation times. Theory and Methods Comparisons of four different voxel‐by‐voxel fitting methods were performed using Monte Carlo simulations, and phantom and ex vivo bovine nasal cartilage (BNC) experiments. In each case, preclinical and clinical imaging field strengths of 7 Tesla (T) and 3T, respectively, and parameters, were investigated across a range of signal‐to‐noise ratios (SNR). Results were compared with Cramér‐Rao lower bound calculations. Results As expected, at high SNR, all methods performed well. At lower SNR, fits explicitly incorporating the analytic form of the Rician noise maintained performance. The much more efficient correction scheme of Gudbjartsson and Patz performed almost as well in many cases. Ex vivo experiments on phantoms and BNC were consistent with simulation results. Conclusion Explicit incorporation of Rician noise greatly improves accuracy and precision in the analysis of biexponential transverse decay data. Magn Reson Med 73:352–366, 2015. © 2014 Wiley Periodicals, Inc.